2018
DOI: 10.3390/ijms19113627
|View full text |Cite
|
Sign up to set email alerts
|

The Protective and Restorative Effects of Growth Hormone and Insulin-Like Growth Factor-1 on Methadone-Induced Toxicity In Vitro

Abstract: Evidence to date suggests that opioids such as methadone may be associated with cognitive impairment. Growth hormone (GH) and insulin-like growth factor-1 (IGF-1) are suggested to be neuroprotective and procognitive in the brain and may therefore counteract these effects. This study aims to explore the protective and restorative effects of GH and IGF-1 in methadone-treated cell cultures. Primary cortical cell cultures were harvested from rat fetuses and grown for seven days in vitro. To examine the protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(85 reference statements)
3
6
0
Order By: Relevance
“…although not fully understood, could be mediated by modifying the action of prooxidative enzymes such as NOX4. This is in agreement with previous studies that have demonstrated that GH has a protective effect on mitochondria [38,39], which are the main source of oxidants within cells. This is the reason why mitochondrial dysfunction leads to a greater generation of hROS, which, in turn, contributes to the presentation of a senescent phenotype in ECs and to the activation of redox-sensitive transcription factor nuclear factor-kappa B (NF-κB) [40], which decreases endothelium-induced vasodilation and increases the expression of inflammatory genes in the vasculature of aged rats and elderly humans [41,42].…”
Section: Introductionsupporting
confidence: 93%
“…although not fully understood, could be mediated by modifying the action of prooxidative enzymes such as NOX4. This is in agreement with previous studies that have demonstrated that GH has a protective effect on mitochondria [38,39], which are the main source of oxidants within cells. This is the reason why mitochondrial dysfunction leads to a greater generation of hROS, which, in turn, contributes to the presentation of a senescent phenotype in ECs and to the activation of redox-sensitive transcription factor nuclear factor-kappa B (NF-κB) [40], which decreases endothelium-induced vasodilation and increases the expression of inflammatory genes in the vasculature of aged rats and elderly humans [41,42].…”
Section: Introductionsupporting
confidence: 93%
“…This is what happens in patients with GHD, but it is normalized after replacement therapy with GH [13]. This is in agreement with previous studies that demonstrate that GH has a protective effect on mitochondria [41,42], which are the main source of oxidants within cells and a main objective of oxidative stress, but also produce elimination systems of oxidants. This is the reason why mitochondrial dysfunction leads to a greater generation of hROS which, in turn, contributes to the presentation of a senescent phenotype in ECs and to the activation of redox-sensitive transcription factor NF-kß [43], that decreases endothelialinduced vasodilation and increases the expression of inflammatory genes in the vasculature of aging rats and humans [44,45].…”
Section: Figuresupporting
confidence: 91%
“…Meanwhile, GH and IGF-1 in circulation have been shown to cross the blood-brain barrier into the brain tissue and cerebrospinal fluid (CSF) to activate GH/IGF-1 receptors [3,[6][7][8]. The potential roles of GH and IGF-1 in brain growth, development, neurogenesis, and neuroprotection, as well as their functional roles in behavior, cognition and neurotransmission, have been investigated in vivo and in vitro [9][10][11][12]. For instance, GH or IGF-1 gene knock-out mice, compared to control animals, exhibited CNS deficits including reduced brain size, loss of myelination and specific parvalbumincontaining neurons, and cognitive impairments [13,14].…”
Section: Introductionmentioning
confidence: 99%